2021
DOI: 10.1111/his.14350
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal squamous cell carcinoma: p16/p53 immunohistochemistry as a strong predictor of HPV tumour status

Abstract: Aims Oropharyngeal squamous cell carcinomas (OPSCC) related to human papillomavirus (HPV) infection have a better prognosis than those without HPV infection. Although p16INK4a overexpression is used as a surrogate marker for HPV infection, 5–20% of p16‐positive OPSCC are described as being unrelated to HPV infection, with worse overall survival compared to OPSCC‐related HPV. There is therefore a risk of undertreating a proportion of OPSCC patients falsely considered to be HPV‐driven because of p16 positivity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Notably, if the HPV-related OPSCC rate is extremely variable, in the series where p16 IHC and nucleic acid detection are both performed, the false positive rate (FPR) of p16 IHC among HPV-negative cases is between 5 and 20% [ 11 , 18 , 35 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], and is pretty constant for a given assay even in different populations (such as Dutch and Sardinians) (ISH, DNA detection without amplification, PCR) (some examples are shown in Table 2 ). When the current standard for the diagnosis of HPV-driven carcinogenesis is used (mRNA detection or sequential p16IHC and HPV-DNA PCR), the rate of HPV-negative OPSCC expressing p16 is notably always about 5.5% [ 11 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, if the HPV-related OPSCC rate is extremely variable, in the series where p16 IHC and nucleic acid detection are both performed, the false positive rate (FPR) of p16 IHC among HPV-negative cases is between 5 and 20% [ 11 , 18 , 35 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], and is pretty constant for a given assay even in different populations (such as Dutch and Sardinians) (ISH, DNA detection without amplification, PCR) (some examples are shown in Table 2 ). When the current standard for the diagnosis of HPV-driven carcinogenesis is used (mRNA detection or sequential p16IHC and HPV-DNA PCR), the rate of HPV-negative OPSCC expressing p16 is notably always about 5.5% [ 11 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…TP53 mutations are highly prevalent in OPSCC, unrelated to HPV infection but driven by mutagenic substances present in tobacco and alcohol [ 46 ]. Accordingly, it is well established that tobacco/alcohol-associated carcinogenesis is correlated to p53 mutations whereas in HPV-driven HNSCCs in the majority of cases, wild-type (wt) p53 can be detected [ 47 ]. Therefore, in smoking HNSCC patients, which seem to be more common in Germany than in the USA (see Section 4 ), for instance, it might be helpful to distinguish via p53 analysis between tumors that rather are HPV-driven (wt-p53) or indeed associated with tobacco-associated carcinogenesis (mutant p53) [ 48 , 49 ].…”
Section: Detection Methodsmentioning
confidence: 99%
“…Therefore, in smoking HNSCC patients, which seem to be more common in Germany than in the USA (see Section 4 ), for instance, it might be helpful to distinguish via p53 analysis between tumors that rather are HPV-driven (wt-p53) or indeed associated with tobacco-associated carcinogenesis (mutant p53) [ 48 , 49 ]. Hence, and to overcome the aforementioned problem correlated to p16 INK4A IHC for HPV detection as described in 3.1, Benzerdjeb and colleagues [ 47 ] conducted a study on 110 OPSCC combining p16 INK4A IHC and p53 analysis in terms of detection of wt-p53 versus mutant p53. For p16 INK4A -positive or p16 INK4A -negative/wt-p53 cases (n = 63), DNA in situ hybridisation for high-risk HPV was performed, and if negative, the HPV status was controlled by HPV DNA PCR (n = 19).…”
Section: Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggest that these factors could be used for a better stratification and management of this category of patients [35]. A research team from Lyon used p16/p53 algorithm to predict HPV tumor status in OPSCC, and authors from Germany concluded that tobacco, alcohol abuse, age, and gender should be added to the current UICC (The Union for International Cancer Control) staging system to improve the risk stratification in HPV+ OPSCC [13,36]. Korsten LHA et al from Amsterdam evaluated the health-related quality of life for HPV-positive OPSCC patients.…”
Section: Opscc Hpv Dna Positive P16 Risk Factorsmentioning
confidence: 99%